How repeatable is PAPE effect: the impact of in-season isometric squat activation on countermovement jump performance enhancement in national level soccer players - Jarosz, J.; Gawel, D.; Grycmann, P.; Aschenbrenner, P.; Spieszny, M.; Wilk, M.; Krzysztofik, M. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background The post-activation performance enhancement (PAPE) effect has been widely studied; however, its repeatability across training sessions during the competitive season in team sports has not yet been verified. Therefore, this study investigates whether PAPE effect, as measured by the countermovement jump (CMJ) without arm swing, induced by an maximum voluntary isometric squat as a conditioning activity (ICA) three days after the match, could be replicated over a 4-week training period throughout the season. The study also explores whether the magnitude of acute PAPE responses correlates with match running variables, as monitored by global positioning system (GPS) data.